DNA methylation-driven genes in hepatocellular carcinoma patients: insights into immune infiltration and prognostic implications - Zhi Zhang; Tongling Zhao; Weida Meng; Jiahao Chen; Chengyi He; Xing Sun; Hai Huang (Frontiers in Medicine)
BackgroundHepatocellular carcinoma (HCC) poses a significant global burden as a highly prevalent and life-threatening malignant tumor that endangers human life and wellbeing. The purpose of this study was to examine how DNA methylation-driven genes impact the prognosis of HCC patients.MethodsDifferentially expressed genes from The Cancer Genome Atlas, GSE76427, GSE25097 and GSE14520 datasets were collected to perform differential expression analysis between HCC patients and controls. Weighted gene coexpression network analysis (WGCNA) was subsequently performed to create coexpression modules for the DEGs. Then, ssGSEA was employed to investigate the infiltration of immune cells in HCC. Enrichment analysis and methylation were carried out for the module genes. We utilized Kaplan–Meier survival analysis to assess patient prognosis.ResultsEight coexpression modules were identified via WGCNA for 1927 upregulated and 1,231 downregulated DEGs, after which the hub genes of the modules were identified. Module 5 had high immune infiltration, and the hub gene SCAMP3 was positively associated with Tcm. Module 3 exhibited a low level of immune infiltration, and the expression of the hub gene HCLS1 was negatively correlated with T cells and dendritic cells. Furthermore, we obtained five hub genes (BOP1, BUB1B, NOTCH3, SCAMP3, and SNRPD2) as methylation-driven genes. BOP1 and BUB1B were found to be correlated with unfavorable overall survival in patients with HCC.ConclusionHCLS1 and SCAMP3 are associated with immunity, whereas BOP1 and BUB1B are modified by methylation and may serve as prognostic markers for HCC.